2015
DOI: 10.3109/03630269.2015.1071268
|View full text |Cite
|
Sign up to set email alerts
|

Frequencies of HKααand anti-HKααAlleles in Chinese Carriers of Silent Deletionalα-Thalassemia

Abstract: The HKαα (HongKongαα) allele is an unusual rearrangement of the α-globin gene cluster containing both the -α(3.7) (rightward) and ααα(anti 4.2) crossover deletion/duplication. The anti-HKαα (anti-HongKongαα) allele is the reciprocal product containing both the -α(4.2) (leftward) and ααα(anti 3.7) unequal crossover deletion/duplication. In clinical practice of thalassemia screening, gap-polymerase chain reaction (gap-PCR) approaches are used to detect the common -α(3.7) and -α(4.2) deletions of α-thalassemia (α… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 13 publications
1
12
0
Order By: Relevance
“…In the case of Mut-05, the α-globin triplication combined with the b-globin gene mutation (CD17 (AAG > TAG)) apparently failed to cause thalassemia, suggesting that other mechanism(s) must exist and meriting further investigation. In addition, 18 cases of the HK αα, and 1 case of the ααα anti3.7 /--SEA did not presented any clinical manifestations such as anemia at the time of examination, which is consisted with previous reports [21,22].…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…In the case of Mut-05, the α-globin triplication combined with the b-globin gene mutation (CD17 (AAG > TAG)) apparently failed to cause thalassemia, suggesting that other mechanism(s) must exist and meriting further investigation. In addition, 18 cases of the HK αα, and 1 case of the ααα anti3.7 /--SEA did not presented any clinical manifestations such as anemia at the time of examination, which is consisted with previous reports [21,22].…”
Section: Discussionsupporting
confidence: 79%
“…The HKαα genotype was rst described by Wang [20]; then, Shang et al rst reported that the population prevalence of HKαα was 0.07% and that of anti-HKαα was 0.02% in Guangxi province of China [21]. Afterwards, the population prevalence of HKαα was determined to be 0.07% and that of anti-HKαα to be 0.003% in Guangdong province [22]. The differences between our ndings and the previously reported data could be due to geographical pattern differences and population diversity [23].…”
Section: Discussionmentioning
confidence: 99%
“…To date, there are few reports pertaining to HKαα/αα type thalassemias, which are mainly detected in Guangdong and Guangxi, China 4,5 . It has been found that the hematological manifestations is better in the HKαα/αα allele carriers than in the –α 3.7 carriers 19 . Previous studies have demonstrated that α-globin triplication is not rare in humans 2022 ; however, the anti4.2 fragment cannot be directly detected by the currently available commercial kits 23 .…”
Section: Discussionmentioning
confidence: 99%
“…Further confirmation will be necessary using 2-round nested PCR analysis or by pedigree analysis. 20 In Chinese carriers of silent deletional α-thalassaemia the frequencies of the HKαα and anti-HKαα alleles were 2.27% and 0.35% in -α 3.7 and -α 4.2 carriers, respectively. 20 Given the rarity of the HKαα and anti-HKαα alleles, a routine screening for these two rearrangements is not necessary on most occasions.…”
Section: Methodsmentioning
confidence: 99%
“…19 A two-round nested PCR strategy was carried out to detect the possible presence of HK αα, a rare α- thalassaemia mutation, which has been reported in southern Chinese subjects. 20,21…”
Section: Methodsmentioning
confidence: 99%